2013
DOI: 10.1111/j.1541-0420.2012.01823.x
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Individual Predictions of Prostate Cancer Recurrence Using Joint Models

Abstract: Summary Patients who were previously treated for prostate cancer with radiation therapy are monitored at regular intervals using a laboratory test called Prostate Specific Antigen (PSA). If the value of the PSA test starts to rise, this is an indication that the prostate cancer is more likely to recur, and the patient may wish to initiate new treatments. Such patients could be helped in making medical decisions by an accurate estimate of the probability of recurrence of the cancer in the next few years. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
139
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(139 citation statements)
references
References 15 publications
0
139
0
Order By: Relevance
“…For example, if the risks of upgrading and treatment initiation both increase with PSA velocity, the two risks will be positively correlated. In practice, we estimate a so-called joint model for the evolution of the patient variables and the risks of upgrading and treatment initiation (1315). After fitting the joint model, we extract the risk of upgrading in the absence of competing treatments using standard statistical formulas for obtaining marginal from conditional data summaries.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…For example, if the risks of upgrading and treatment initiation both increase with PSA velocity, the two risks will be positively correlated. In practice, we estimate a so-called joint model for the evolution of the patient variables and the risks of upgrading and treatment initiation (1315). After fitting the joint model, we extract the risk of upgrading in the absence of competing treatments using standard statistical formulas for obtaining marginal from conditional data summaries.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…[22] and [38], with different joint modeling approaches, showed that accounting for longitudinal PSA measures was a powerful tool for individual prediction. [31], following the joint modeling work of [22], implemented real-time predictions of PCa recurrence on a web-based calculator. In the early detection area, several studies have assessed the predictive value of dynamic PSA markers like PSA velocity, PSA doubling time or PSA percentual change.…”
Section: Discussionmentioning
confidence: 99%
“…Joint models constitute a valuable tool that can be used to derive such probabilities and also provide predictions for future biomarker levels. More specifically, under the Bayesian specification of the joint model, presented in Section 2, we can derive subjectspecific predictions for either the survival or longitudinal outcomes (Yu, Taylor, and Sandler 2008;Rizopoulos 2011Rizopoulos , 2012Taylor, Park, Ankerst, Proust-Lima, Williams, Kestin, Bae, Pickles, and Sandler 2013). To put it more formally, based on a joint model fitted to a sample D n = {T i , δ i , y i ; i = 1, .…”
Section: Definitions and Estimationmentioning
confidence: 99%
“…More details can be found in Yu et al (2008), Rizopoulos (2011Rizopoulos ( , 2012, and Taylor et al (2013).…”
Section: Definitions and Estimationmentioning
confidence: 99%